Deprescribing as a strategy for improving safety of medicines in older people: Clinical and regulatory perspective - Crisafulli, Salvatore; Poluzzi, Elisabetta; Lunghi, Carlotta; Di Francesco, Vincenzo; Pellizzari, Luca; Pasina, Luca; Elli, Chiara; Trotta, Francesco; Cangini, Agnese; Trevisan, Caterina; Zazzara, Maria Beatrice; Onder, Graziano; et al. (Frontiers in Drug Safety and Regulation, 2022)
The ageing process is associated with an increased probability of accumulating health deficits, chronic conditions and geriatric syndromes, leading to a growing prevalence of multimorbidity, defined as the co-occurrence of two or more chronic conditions (of which, at least one physical condition). One of the most frequent and direct consequences of multimorbidity, especially amongst older adults, is polypharmacy, a condition characterized by the concomitant use of five or more drugs per day. Polypharmacy is one of the main risk factors for adverse clinical outcomes, including drug-drug interactions and adverse drug reactions, also resulting in increased hospitalizations, morbidity, and increased use of healthcare resources, with considerable implications for healthcare costs. Deprescribing is one of potential approaches to reduce inappropriate prescribing and it is defined as the stopping or dose reduction of medications that are either inappropriate or unnecessary, especially among patients with polypharmacy. In this review, the major issues associated with polypharmacy among older people, the current guidelines for the management of polypharmacy and the strategies to implement deprescribing in different settings (i.e., hospital setting, nursing homes and general practice) are discussed.